Detection of β-thalassemia/hemoglobin E disease in samples which initially were diagnosed as homozygous hemoglobin E - Sakorn Pornprasert (2018)
Background: Differentiation of β-thalassemia/HbE disease from homozygous HbE in samples containing HbA 2 /E > 75% and HbF < 15% is difficult. The aim of this study is to observe the possibility of using Hb typing and hematological parameters to identify both disorders. Methods: Multiplex amplification refractory mutation system (MARMS)-PCR for β-thalassemia codons 17 (A > T), 41/42 (-TCTT), 71/72 (+A), and IVSI-nt1 (G > T) mutations and ARMS-PCR for HbE were performed in 67 samples that contained HbA 2 /E > 75% and HbF < 15%. Results: β-thalassemia/HbE disease was identified in 10 of 67 (14.93%) samples. Levels of hemoglobin, hematocrit, and mean corpuscular volume (MCV) of β-thalassemia/HbE disease were significantly lower than those of homozygous HbE whereas, levels of HbF were significantly higher. Conclusions: In places where the molecular analysis is not available, HbF > 5% in combination with MCV < 55 fL, hemoglobin < 100 g/L, and hematocrit < 0.30 L/L could be used for screening of β-thalassemia/HbE disease.